2011
DOI: 10.5588/ijtld.10.0303
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of asthma and atopy in the Canary Islands, Spain

Abstract: This study shows a high prevalence of sensitisation to mites, atopy, BHR and asthma in the Canaries, similar to that observed in English-speaking countries. We suggest that these findings could partially result from climatic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…However, so far there are no population-based studies providing information on sensitization to BT and its relation to asthma or other allergic diseases. In addition, in a previous study we reported a higher prevalence of asthma in the Canaries than in the other Spanish centers in the ECRHS, something that was attributed to the temperate climate of the region (6). In order to address this lack of information, and applying the same methodology used in the ECRHS, in this study, we have analyzed the prevalence of sensitization to BT in the Canaries in a random sample of adult subjects, aged 20-44, and its relation to asthma, asthma-related symptoms, rhinitis, and atopic dermatitis.…”
Section: Introductionmentioning
confidence: 87%
“…However, so far there are no population-based studies providing information on sensitization to BT and its relation to asthma or other allergic diseases. In addition, in a previous study we reported a higher prevalence of asthma in the Canaries than in the other Spanish centers in the ECRHS, something that was attributed to the temperate climate of the region (6). In order to address this lack of information, and applying the same methodology used in the ECRHS, in this study, we have analyzed the prevalence of sensitization to BT in the Canaries in a random sample of adult subjects, aged 20-44, and its relation to asthma, asthma-related symptoms, rhinitis, and atopic dermatitis.…”
Section: Introductionmentioning
confidence: 87%
“…The Canary Islands have a very high incidence of allergic diseases. Although allergic comorbidity is a multifactorial pathology, the existence of other unknown factors that influence the high incidence in the Canaries is recognized [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of asthmatic adults in the Canary Islands is significantly higher when compared to the national average (17.2% and 5.7%, respectively) [ 9 , 10 , 11 , 12 ]. In children, results are similar and prevalence of asthma (18.4%), rhinitis (40.3%) and allergic dermatitis (35.8%) are higher than the national averages [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations